2021
DOI: 10.1038/s41598-020-80896-9
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral activity of lambda-carrageenan against influenza viruses and severe acute respiratory syndrome coronavirus 2

Abstract: Influenza virus and coronavirus, belonging to enveloped RNA viruses, are major causes of human respiratory diseases. The aim of this study was to investigate the broad spectrum antiviral activity of a naturally existing sulfated polysaccharide, lambda-carrageenan (λ-CGN), purified from marine red algae. Cell culture-based assays revealed that the macromolecule efficiently inhibited both influenza A and B viruses with EC50 values ranging from 0.3 to 1.4 μg/ml, as well as currently circulating severe acute respi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(87 citation statements)
references
References 40 publications
2
85
0
Order By: Relevance
“…Products A and B contain carrageenans (Table 1), which are sulfated polysaccharides isolated from red seaweeds previously shown to exert antiviral activity (14,(21)(22)(23)(24)(25). Product A contains i-carrageenan (1.2 mg/mL) and κ-carrageenan (0.4 mg/mL), and product B contains i-carrageenan only (1.2 mg/mL).…”
Section: Resultsmentioning
confidence: 99%
“…Products A and B contain carrageenans (Table 1), which are sulfated polysaccharides isolated from red seaweeds previously shown to exert antiviral activity (14,(21)(22)(23)(24)(25). Product A contains i-carrageenan (1.2 mg/mL) and κ-carrageenan (0.4 mg/mL), and product B contains i-carrageenan only (1.2 mg/mL).…”
Section: Resultsmentioning
confidence: 99%
“…In the early face of a pandemic where only hygienic measures and confinements are the options to stop the spread of infections among the affected population, either repurposed synthetic drugs or natural substances with a broadly acting antiviral capacity are the only options for therapeutic intervention. Similar to quinine, the natural substance iota-carrageenan was shown to interfere with SARS-CoV-2 replication in vitro [56][57][58]. For this polysaccharide isolated from red algae, which can be used as a prophylactic nasal and throat spray or as a lozenge, first clinical trials in Austria, the United States, Argentina, and Great Britain have been reported, and first positive results have been published [56,59,60].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Bansal et al confirmed the antiviral activity of iota-carrageenan nasal spray in vitro using Vero E6 cells [67]. Lambda-carrageenan showed the potent inhibition of SARS-COV-2 in vitro in Vero cells, preventing the viral attachment to cell receptors [64].…”
Section: Coronavirusesmentioning
confidence: 96%
“…Lambda-carrageenan inhibited both influenza A and B viruses in vitro on MDCK cells along with infected mouse models. This molecule has shown its effect by preventing the viral attachment to cell receptors [64].…”
Section: Influenza Virusmentioning
confidence: 99%